Accumulation o f lead and cadmium in vegetables and farmland near Hoa Khanh industrial zone, Da Nang city - Minh, Vo Van; Khanh, Nguyen Van; Anh, Dam Minh; Vinh, Tran Duy (VNU Journal of Science: Earth and Environmental Sciences; Vol 28 No 3, 2012)
Abstract: